1998
DOI: 10.1093/humrep/13.8.2107
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound tracking of the movement of embryo-associated air bubbles on standing after transfer

Abstract: The aim of this study was to investigate whether standing upright shortly after embryo transfer has any potential to affect the position of embryos transferred to the uterine cavity during treatment with in-vitro fertilization (IVF). This was assessed by ultrasound-guided tracking of embryo-associated air within the uterine cavity. A prospective study of 93 patients undergoing 101 consecutive embryo transfers in an IVF programme was carried out. Transvaginal ultrasound guided embryo transfer was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 12 publications
0
26
0
3
Order By: Relevance
“…Woolcott and Stanger [7] showed that immediate ambulation shortly after embryo transfer does not influence the final position of embryo-associated air bubble. But there were no studies comparing air bubble location at transfer and a short period later, in patients remaining in the horizontal position and immediately ambulated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Woolcott and Stanger [7] showed that immediate ambulation shortly after embryo transfer does not influence the final position of embryo-associated air bubble. But there were no studies comparing air bubble location at transfer and a short period later, in patients remaining in the horizontal position and immediately ambulated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some showing an improvement in outcome (Al-Shawaf et al, 1993;Ivanovski et al, 2006;Kan et al, 1999;Kojima et al, 2001;Woolcott et al, 1998 ), others demonstrating no difference De Camargo et al, 2004;Garcia-Velasco et al, 2002;Li et al, 2005;Lindheim et al, 1999;Mirkin et al, 2003;Prapas et al, 1995 ) and others with mixed results (Fisser et al, 2006;Hurley et al, 1991;Prapas et al, 2001). No study has shown a worsening of outcome when ultrasonography is used.…”
Section: Resultsmentioning
confidence: 99%
“…Of all embryo(s) that implant successfully, 81% does so in the area where the air bubbles were initially seen on embryo transfer [28]. It is demonstrated that the air bubbles did not move after immediate ambulation after transfer in 94.1% of the cases [37] and this is confirmed by our study group [38]. We agree there is a lack of knowledge about positioning of the embryo(s) during and after embryo transfer in the uterine cavity, independently using a simple syringe or a new device.…”
Section: Discussionmentioning
confidence: 99%